Design and Experimentation on Mixed Mode Natural Convection Solar Dehydrator for Ocimum Sanctum - Husainy, Avesahemad S. N.; Panade, Amey A.; Birnale, Anuj A.; Kadage, Yuvraj R. (Asian Review of Mechanical Engineering, 2018)
Tulsi (Ocimum Sanctum) is also known as “the elixir of life” since it promotes longevity. Different parts of plant are used in Ayurveda and Siddha Systems of Medicine for prevention and cure of many illnesses and everyday ailments like common cold, headache, cough, flu, earache, fever, colic pain, sore throat, bronchitis, asthma, hepatic diseases, malaria fever, as an antidote for snake bite and scorpion sting, flatulence, migraine headaches, fatigue, skin diseases, wound, insomnia, arthritis, digestive disorders, night blindness, diarrhea and influenza. We can use Tulsi in Powder form, Oil extract, etc. Drying of such kind of Ayurvedic leaves is essential for their further use. Drying is the technique in which moisture of that product removed under standard condition. Conventionally drying is done in open area but there are so many disadvantages of it viz, infection by dust and durt, the product may be contacted with bird’s excreta, dead insects, etc. In order to prevent such product, solar drying is the best technique. In solar drying method we are not only dry the product but also we can reduce the drying time and produce the hygienic product. Solar dryer have shown a very good result in the preservation of the ginger from wastage, poisoning and other contaminants. The solar dryer is solely depending on the renewable energy of the sun. It does not use any fossil fuel for burning.